WOMEN FARMERS GROUP AS PEER EDUCATOR IN PREVENT HYPERTENSION - Fitria Saftarina (Majalah Kedokteran Sriwijaya, 2022)
The results of the 2018 Basic Health Research, farmers have a higher proportion of hypertension than other occupations, namely 36.14%. One of the characteristics of the farming population is the low level of education. These factors contribute to the low implementation of healthy living behavior, especially in the prevention of hypertension. Women farmer groups play an important role as peer educators who can implement hypertension prevention behavior in their families and their environment. This study aims to increase knowledge about preventing hypertension in women's farmer groups in Karanganyar District, South Lampung Regency. The benefit of this study is the implementation of healthy living behavior to prevent hypertension. The activity was carried out with a target of 194 people who are members of 10 women farmer groups. The intervention is health education about hypertension prevention. The results obtained, before the education was carried out, the knowledge of farmers was not good as many as 106 people (54,6%) and after education the knowledge of farmers was not good as many as 14 people (7,2%). From the results of McNemar's analysis, it was found that there was a significant difference between knowledge before and after health education (p = 0.001). Health education carried out continuously as an effort to maintain health in the farming community in Karanganyar District, Lampung Regency, Lampung.